Brief recommendations for participation in competitive sports of athletes with arterial hypertension: Summary of a Position Statement from the Sports Cardiology Section of the European Association of Preventive Cardiology (EAPC). (29th August 2020) - Niebauer, Josef; Börjesson, Mats; Carre, Francois; Caselli, Stefano; Palatini, Paolo; Quattrini, Filippo; Serratosa, Luis; Adami, Paolo E; Biffi, Alessandro; Pressler, Axel; Rasmusen, Hanne K; Schmied, Christian; et al.
Abstract: Owing to its undisputed multitude of beneficial effects, European Society of Cardiology guidelines advocate regular physical activity as a class IA recommendation for the prevention and treatment of cardiovascular disease. Nonetheless, competitive athletes with arterial hypertension may be exposed to an increased risk of cardiovascular events. Guidance to physicians will be given in this summary of our recently published recommendations for participation in competitive sports of athletes with arterial hypertension.